1998
DOI: 10.1021/cm9802043
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State NMR Structural Studies of the Ternary Molybdenum Cluster Chalcogenides CdxMo6Se8 (x = 1, 2)

Abstract: The structures of the ternary Chevrel phases CdMo 6 Se 8 and Cd 2 Mo 6 Se 8 have been studied by several complementary 111 Cd NMR spectroscopic techniques. Specifically, cadmium mobility and bonding properties are probed by temperature and frequency dependent measurements of static line shapes, magic angle spinning (MAS) NMR spectra, and spinlattice relaxation rates. Furthermore, models for the spatial cadmium distribution are tested on the basis of 111 Cd-111 Cd dipole-dipole interactions, measured by spin-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“… a The interpretation of the experimental data related to Cd 2+ insertion into Mo 6 S 8 differs from that of ref , , and (see text). …”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“… a The interpretation of the experimental data related to Cd 2+ insertion into Mo 6 S 8 differs from that of ref , , and (see text). …”
Section: Introductionmentioning
confidence: 93%
“…This suggestion agrees well with most of the synthetic results, which showed that CPs of group I could be obtained only at high temperatures, in contrast to CPs of group II, which can be produced by chemical or electrochemical reversible reactions as well at ambient temperatures. However, our analysis of available experimental data ,− ,,− , (Tables and ) demonstrates that the ion-transport behavior in CPs is much more complex; it includes (i) apparent immobility of the large M cations like Pb 2+ , Sn 2+ , Ag + in the ternary phases, MMo 6 T 8 ; (ii) coupled M + M′ diffusion in the quaternary phases, M x M′ y Mo 6 T 8 , where both large and small cations can assist; (iii) cation trapping in the Mg−Mo 6 S 8 , Cd−Mo 6 S 8 , and Na−Mo 6 T 8 systems; (iv) a combination of low and high rate diffusion kinetics at the first and last intercalation stages, respectively, for the Cu−Mo 6 S 8 , Mn−Mo 6 S 8 , and Cd−Mo 6 Se 8 systems; and (v) a fast ionic transport for small cations like Ni 2+ , Zn 2+ , and Li + . Thus, contrary to general expectation, there is no unambiguous correlation between the cation mobility and its size.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The remarkable ionic conductivity of Chevrel phases (CPs), M x Mo 6 T 8 (M = metal, T = S, Se,Te) remains in the shadow of their striking superconductivity. However, CPs are, at present, the only materials that allow fast and reversible insertion of various cations, monovalent (Li + , Na + , Cu + ) as well as divalent Zn 2+ , Cd 2+ , Ni 2+ , Mn 2+ , Co 2+ , Fe 2+ , and Mg 2+ at ambient temperatures. Moreover, the insertion of an M cation into metal-containing CPs, M′ x Mo 6 T 8 ( x ≠ 0), may result in the displacement reaction associated with an unusual coupled M + M′ cation motion in the same crystal structure. , The key question here is what is so special in CPs that ensures the exceptionally high mobility of multivalent cations?…”
Section: Introductionmentioning
confidence: 99%
“…There have been very few reports of solid-state 111 Cd and/or 113 Cd nuclearmagnetic-resonance ͑NMR͒ relaxation studies. Spin-lattice relaxation times T 1 have been reported in the pure metal, 4,5 in Cd x Mo 6 Se 8 ͑x =1,2͒, 6 and in a variety of doped semiconductor crystals. 7,8 In the experiments reported here, 111 Cd and 113 Cd spectra and magnetization recoveries for CdMoO 4 were observed using static samples with a Bruker MSL-300 NMR spectrometer at a magnetic field of 7.049 T, where the proton resonance frequency is 300.130 MHz.…”
mentioning
confidence: 99%